Association of serum copper, zinc level in invasive cervical cancer in a tertiary hospital - Akter, Naznine; Hossain, Fawzia; Naher, Syfun; Khatoon, Farhana; Meher, Subrina; Sayed, Sunzia; Nihar, Fatema; Akther, Moushume (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Cervical cancer remains a significant global health concern. The present study was conducted to assess the relationship between serum copper and zinc levels in individuals diagnosed with cervical cancer. The aim of this study was to assess the association between serum copper and zinc levels in invasive cervical cancer in a tertiary hospital. Methods: This case-control study was conducted among 122 women, aged 25-65, attending the outpatient department and Colposcopy Clinic of the Department of Gynecological Oncology, BSMMU, Dhaka, from April 2022 to March 2023. The cases (n=61) had histopathologically confirmed cervical cancer, while the controls (n=61) had normal cervixes. Serum copper and zinc levels were measured at the Laboratory of Biochemistry and Molecular Biology, BSMMU. Data were analyzed using Microsoft Excel and SPSS v27.0. Results: The study revealed that cervical cancer cases had significantly higher serum copper levels and a 6.4 times higher risk when copper levels were ≥140.0 mcg/dl. Serum zinc levels were significantly lower in cases, with a 3.9 times higher risk when zinc levels were <68 mcg/dl. Additionally, the Cu/Zn ratio was higher in cases, and a ratio >1.87 conferred a 4.5 times higher risk of cervical carcinoma. Conclusions: Elevated copper, reduced zinc, and a higher copper-zinc ratio were observed in cervical cancer patients, suggesting a potential association with cervical cancer risk and warranting further investigation for clinical applications in early detection and management.